Effect of technical mistakes on arm coordination in backstroke - Chollet, D.; Carter, M.; Seifert, L. (Biomechanics and Medicine in Swimming X, 2006)
This study quantified the influence of two technical mistakes, the band entry outside of the shoulder axis and head flexion on the thorax, on arm coordination in backstroke, with increases in velocity. Sixteen national level swimmers simulated these two mistakes, often observed in non-expert swimmers, individ-ually and in combination at fbur race paces. They also swarn with a traditional technique at the four paces. An adaptation of the Index of Coordination (IdC) (3) allowed the inter-arm coordination to be quantified in backstroke. In each swim con-dition, the negative values of IdC confirmed a catch-up coordination. This coordination was influenced by the mistakes adopted by the swimmers because, when the two mistakes were associated, the arm coordination was most disturbed.